Immunomodulatory Effects of Angelica Sinensis Polysaccharides on Juvenile Chinese Sturgeon (Acipenser sinensis): Physiological and Molecular Insights - Jianming Zhang; Tian Tian; Dezhi Zhang; Rui He; Debin Shu; Wei Jiang; Yacheng Hu (Fishes, 2025)
The Chinese sturgeon (Acipenser sinensis) is a critically endangered species with significant ecological and economic value. This study investigates the effects of Angelica sinensis polysaccharides (ASPs) on the antioxidant and immune responses of juvenile Chinese sturgeon through physiological and molecular approaches. Healthy juvenile Chinese sturgeon (n = 120, mean body weight 356.50 ± 92.87 g) were fed diets supplemented with 0%, 0.5%, 1.0%, and 2.0% ASP for 36 days. Results showed that ASP, particularly at 2.0%, significantly enhanced serum antioxidant capacity by increasing activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and reduced malondialdehyde (MDA) content. Immune indices, including immunoglobulins (IgG and IgM), complement components (C3 and C4), lysozyme (LSZ) activity, and antimicrobial peptides (AMPs), were also significantly elevated in the 1.0% and 2.0% ASP groups. Transcriptome sequencing of spleen and kidney tissues from the control and 2.0% ASP groups identified 151 and 467 differentially expressed genes (DEGs), respectively, with significant enrichment in immune-related pathways such as phagocytosis and the MAPK signaling pathway. Ten candidate immune-related genes (e.g., PDIA4, H-2Q9α, TTC39B) were validated by qRT-PCR, confirming the reliability of the RNA-seq data. This study demonstrates that ASP can enhance the antioxidant and immune responses of juvenile Chinese sturgeon, providing a potential natural immunostimulant for aquaculture. These findings offer a scientific basis for the conservation and sustainable production of this endangered species and highlight the need for further research on the application of ASP in sturgeon aquaculture.

Hawthorn Polysaccharide Enhances Growth, Immunity, and Intestinal Health in Crucian Carp (Carassius auratus) Challenged with Aeromonas hydrophila - Liang Luo; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Cheng Zhao; Baoquan He; Wei Wang; Wenhua Wu (Fishes, 2025)
Bacterial disease infections pose a major challenge to the healthy growth of crucian carp. Hawthorn polysaccharide (HP) is a natural active ingredient in hawthorn and has a wide range of pharmacological effects. However, the mechanism of HP against Aeromonas hydrophila infection in crucian carp cultures is unknown. In this study, it was found that 0.4% HP could significantly reduce the mortality of crucian carp, significantly increase the activities of T-AOC, SOD, CAT, and GSH-PX of crucian carp infected with A. hydrophila (p

Microplastics Induce Structural Color Deterioration in Fish Poecilia reticulata Mediated by Oxidative Stress - Hong-Yu Ren; Huan-Chao Ma; Rui-Peng He; Cong-Cong Gao; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (Fishes, 2025)
Microplastics (MPs) can affect fish health by inducing oxidative stress, but their impact on structural coloration remains poorly understood. This study investigated the effects of environmentally relevant concentrations (16 and 160 μg/L) of MPs and nanoplastics (NPs) exposure on growth, oxidative stress and structural coloration in blue strain guppy fish (Poecilia reticulata). Results showed exposure to 160 μg/L MPs significantly reduced specific growth rate of fish compared to controls. Plastic accumulation followed a dose-dependent pattern, especially within gut concentrations. Oxidative stress responses differed between MPs and NPs: 160 μg/L MPs decreased SOD activity in skin and reduced GSH levels, while 160 μg/L NPs increased MDA levels in gut tissues, indicating severe lipid peroxidation. Structural coloration analysis revealed exposure to 160 μg/L MPs decreased lightness and increased yellowness, demonstrating reduced blue coloration. This was accompanied by an increase in skin uric acid content, suggesting that guanine conversion might occur to combat oxidative stress. These findings demonstrate that MPs, particularly at high concentrations, impair growth and induce oxidative stress in guppies. To counteract stress, guanine in iridophores may be converted into uric acid, leading to a decline in structural coloration. This study is the first to reveal that MPs disrupt structural coloration of fish, providing new insights into the ecological risks of plastic pollution on aquatic organisms.

Community Dynamics of Fish Larvae in Coastal Zhejiang: Seasonal Variations in Spatiotemporal Distribution and Environmental Driving Factors - Peng Zhao; Rijin Jiang; Qiqun Li; Rui Yin; Yuelian He; Qingxi Han; Guangjie Fang (Fishes, 2025)
The coastal waters of Zhejiang feature a complex aquatic environment and abundant biological resources, creating an ideal habitat for various fish species. However, the systematic monitoring of fish larvae in these offshore waters is limited. This study collected 24,232 fish larvae using large plankton nets during April and November 2022, as well as February and July 2023, and identified 93 species, primarily warm-temperate and warm-water species, with a peak occurrence in summer. The dominant species include Larimichthys croceus, Sebastiscus marmoratus, Lateolabrax japonicus, and Odontamblyopus lacepedii, among others, and these species exhibit frequent seasonal changes. Fish larvae are typically found to be aggregated along estuaries and bays in spring, autumn, and summer, while in winter, they tend to shift towards areas near the boundaries of motor trawler fisheries areas. Our cluster analysis revealed spatial heterogeneity in the community structure, driven by an abundance of dominant and important species. Our Mantel tests and canonical correspondence analysis (CCA) identified seawater temperature and salinity as core drivers of the aggregation and distribution of fish larvae, interacting with factors such as the chlorophyll-a concentration, water turbidity, water depth, and dissolved oxygen. This research provides a scientific basis for the dynamic monitoring of spawning grounds and effective management of fishery resources in Zhejiang’s coastal waters.